Analisis Efektivitas Biaya Pasien PROLANIS DM Tipe 2 di Puskesmas Kota Bandung: Cost Effectiveness Analysis of PROLANIS Patients with DM Type 2 at Bandung Health Centers - Ulyati Ulfah; Eli Halimah; Auliya A Suwantika (Jurnal Sains dan Kesehatan, 2022)
Diabetes mellitus is one of chronic diseases with high treatment cost. Purpose of this research was to analyze the cost-effectiveness of (Prolanis) for patients with type 2 DM and to establish the most significance parameter affecting the cost-effectiveness value. This study is a non-experimental retrospective by collecting medical record data of Prolanis patients with type 2 DM at Bandung Health Center during 2015 and 2016 with 246 samples that met the inclusion criteria. Cost-effectiveness analysis was conducted by calculating Average Cost Effectiveness Ratio (ACER) and Incremental Cost Effectiveness Ratio (ICER). In particular, sensitivity analysis was conducted to investigate the most significance parameter affecting those ratios. The result of unpaired t test confirmed that there was not significance difference on ACER values of 2015 and 2016, whereas the value of arithmetic (0,202) < t table (4,303) with significance value ? 0,04 <0,05. The implementation of Prolanis in 2015 (ACER = Rp. 1.095,97) seemed to be more cost effective than in 2015 (ACER = Rp. 1.268,96). Cost of biguanida drugs is the most influential factor affecting the cost-effectiveness values of Prolanis implementation in patients with type 2 DM in 2015 and 2016.